Peran Guru BK dalam Melaksanakan Manajemen Bimbingan dan Konseling dalam Mengatasi Rendahnya Motivasi Belajar Siswa di SMK Negeri Cikalong - Apit Apit; Irma Nurohmah; Hilmi Fauzi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
Learning motivation is a driving force to improve student learning, both external and internal factors. This research was carried out at Cikalong State Vocational School to determine the role of guidance and counseling teachers in implementing guidance and counseling management to motivate students to learn. The purpose of this research is to find out how guidance and counseling is managed and the efforts made by guidance and counseling teachers at Cikalong State Vocational School in dealing with students who lack motivation to learn. This research uses descriptive qualitative research methods by conducting observations, interviews and documentation with guidance and counseling teachers. After observing, the results of this research can be seen about the role of guidance and counseling teachers at Cikalong State Vocational School in motivating students to learn. The ways to overcome students who lack motivation to learn are by providing guidance to students about the importance of learning, emphasizing the importance of learning throughout life, providing motivation to students and female students by inviting alumni, involving parents and guardians in conveying the importance of learning, providing enrichment and how to deal with problems. exams, use of learning technology.